2001
DOI: 10.4049/jimmunol.167.4.1891
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD4+ and CD8+ T Cells in Allorecognition: Lessons from Corneal Transplantation

Abstract: Corneal transplantation represents an interesting model to investigate the contribution of direct vs indirect Ag recognition pathways to the alloresponse. Corneal allografts are naturally devoid of MHC class II+ APCs. In addition, minor Ag-mismatched corneal grafts are more readily rejected than their MHC-mismatched counterparts. Accordingly, it has been hypothesized that these transplants do not trigger direct T cell alloresponse, but that donor Ags are presented by host APCs, i.e., in an indirect fashion. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 47 publications
3
85
0
1
Order By: Relevance
“…CEC apoptosis mediated by CD4 þ T cells in a non-contact-dependent mechanism could be primarily promoted via secretion of apoptosis-inducing cytokines/molecules. In corneal transplantation, a major subset of CD4 þ T cells are T helper type 1 cells, 4 which are characterized by the expression of their signature cytokine IFN-g, and other proinflammatory cytokines such as TNF-a and IL-1. These proinflammatory cytokines (IFN-g, TNF-a, and IL-1) have been shown to induce apoptosis in CECs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CEC apoptosis mediated by CD4 þ T cells in a non-contact-dependent mechanism could be primarily promoted via secretion of apoptosis-inducing cytokines/molecules. In corneal transplantation, a major subset of CD4 þ T cells are T helper type 1 cells, 4 which are characterized by the expression of their signature cytokine IFN-g, and other proinflammatory cytokines such as TNF-a and IL-1. These proinflammatory cytokines (IFN-g, TNF-a, and IL-1) have been shown to induce apoptosis in CECs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Despite medical advances, immune rejection of corneal grafts remains the most frequent cause of corneal graft failure. 4 Several studies have shown that CD4 þ T cells are the major mediators of acute corneal graft rejection. Corneal endothelial cells (CECs) are the principal targets of alloimmunity in corneal transplantation, which primarily involves allospecific CD4 þ T cells attacking the graft endothelium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three nonexclusive explanations may account for this observation: (a) some evidence has been provided suggesting the possible presence of a very small population of T cells (3%) expressing CD8 intracellularly in CD8 KO mice (26), (b) some non-CD8 + T cells such as natural killer (NK) cells or double-negative T cells may secrete some IFN-γ (27,28), and (c) it is likely that some compensatory mechanisms are present in KO mice. For instance, we have observed previously that in CD4 KO mice one can find more CD4-independent CD8 T cells that produce their own IL-2, thereby compensating for the absence of CD4 + T cell help (29).…”
Section: Differential Contribution Of Cd4 + and Cd8 + T Cells To The mentioning
confidence: 93%
“…50 Thus, corneal transplants can be done with only short-term, topical immunosuppression, partly due to anatomical restrictions of blood and lymph supply, but partly due to tolerogenic effects of MHC class II neg corneal DC. 51 This is associated with the lack of inflammatory CD4 + T cell direct alloresponse. On the other hand, indirect CD4 + T cell responses are regularly detected in mice recipients of fully allogeneic corneas.…”
Section: Immune Status Of Organ/tissuementioning
confidence: 99%